2014
DOI: 10.1245/s10434-014-4085-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Transabdominal Approach Partial Intersphincteric Resection for Low Rectal Cancer: Surgical Feasibility and Intermediate-Term Outcome

Abstract: Laparoscopic APISR can be performed safely and offers similar intermediate-term oncological and functional outcome compared with the open procedure. The oncological adequacy requires long-term follow-up data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 28 publications
6
24
2
5
Order By: Relevance
“…Denost et al 17) demonstrated a significant negative correlation between the WIS score and follow-up duration in 101 patients who underwent ISR. Chi et al 28) reported that continence significantly improved over time based on the relationship between the WIS score and follow-up duration. In the present study, as the WIS score improved over time, the VAS score for bowel movement habits increased, and there was a significant negative correlation between the WIS and VAS scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Denost et al 17) demonstrated a significant negative correlation between the WIS score and follow-up duration in 101 patients who underwent ISR. Chi et al 28) reported that continence significantly improved over time based on the relationship between the WIS score and follow-up duration. In the present study, as the WIS score improved over time, the VAS score for bowel movement habits increased, and there was a significant negative correlation between the WIS and VAS scores.…”
Section: Discussionmentioning
confidence: 99%
“…While the oncological outcomes of ISR do not differ from those of abdominoperineal resection (APR) [2][3][4][5] , longterm functional outcomes and quality of life (QOL) after ISR have not been adequately studied. A few studies of the long-term functional outcomes and QOL after ISR have targeted Asian races, including the Japanese [6][7][8][9][10] . Among studies performed in Western countries, a systematic review by Martin et al 11) showed that perfect continence was achieved in about half of patients who underwent ISR, but that fecal incontinence, which ranged from incontinence to mild soiling to solid stool, occurred in 11%-63% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, a diverting temporary ileostomy was performed in 61 patients (87%), which is created with usual closure of the ileostomy either 1 month postoperative or after completion of adjuvant therapy. In other studies, the rate of diverting ileostomy in ISR ranged between 77% and 90% [10,12]. A temporary stoma is typically used in an attempt to decrease the incidence of perianastomotic infections and the occurrence of muscular fibrosis of the external anal sphincter.…”
Section: Discussionmentioning
confidence: 99%
“…El margen de resección distal en nuestro estudio tuvo una mediana 10 (4-25) mm, Martín et al 7 , informan un promedio de 17,1 (10-29) mm y Akagi et al 8 , entre 5-20 mm. Por otra parte en este trabajo la me-diana del número de linfonodos resecados fue de 11 (1-24) que está dentro del rango (1-37) reportado en la literatura internacional 16,[19][20][21][22] .…”
Section: Discussionunclassified